Early recurrences predict late therapy failure after pulsed field ablation of atrial fibrillation. - Plank, Karin; Bordignon, Stefano; Urbanek, Lukas; Chen, Shaojie; Tohoku, Shota; Schaack, David; Hirokami, Jun; Efe, Tolga; Chun, K.R. Julian; Schmidt, Boris (Journal of Cardiovascular Electrophysiology, 2023)
Introduction: Pulsed field ablation (PFA) is a new ablation technology for atrial fibrillation (AF). Data regarding early recurrences of atrial tachyarrhythmia (ERAT) after PFA‐pulmonary vein isolation (PVI) are sparse. Methods: Consecutive patients with symptomatic AF were enrolled to undergo PFA‐PVI. A dedicated catheter delivering bipolar energy (1.9–2.0 kV) was used. Late recurrence (LR) was defined as documented AF/atrial tachycardia (AT) lasting more than 30 s after a 90‐day blanking period. Results: Two hundred and thirty‐one patients (42% female, age 69 ± 12, 55% paroxysmal AF [PAF]) were included in this analysis. Median follow‐up time was 367 days (interquartile range: 253–400). Forty‐six patients (21%) experienced ERAT after a median of 23 days (46% in PAF and 54% in persistent AF [persAF]). Kaplan–Meier estimated freedom of AF/AT was 74.2% at 1 year, 81.8% for PAF, and 64.8% for persAF (p =.0079). Of patients experiencing ERAT, an LR was observed in 54%. There was no significant difference of LR between those who presented with very early ERAT (0–45 days) and those with ERAT (46–90 days) (p =.57). In multivariate analysis, ERAT (hazard ratio [HR]: 3.370; 95% confidence interval [95% CI]: 1.851–6.136; p <.001) and female sex (HR: 2.048; 95% CI: 1.114–3.768; p =.021) were the only independent predictors for LR. Conclusions: ERAT could be recorded in 21% of patients after PFA‐PVI and was an independent predictor for LR. We found no difference in the rate of LRs among patients experiencing ERAT before or after 45 days.